Closure - Suprayitno, Hitapriya (Journal of Infrastructure & Facility Asset Management, 2025)
Journal of Infrastructure & Facility Asset Management Volume 4, Issue 1, April 2022 (e) ISSN 2656-8896 (P) ISSN 2656-890X JIFAM, Vol.3, Issue 3, December 2021 A New Approach to Estimate the Potential Assets Loss due to Dam-Break Event in Indonesia Farrel Wiguna, Doddi Yudianto, Bobby Minola Ginting & Albert Wicaksono The Effect of Addition RAP as Quality Improved for Hot Paved Mixtures Irfan Zhain, Ria Asih Aryani Soemitro & Hitapriya Suprayitno The Socio-economic Transformations in the Peri-urban of Bandung Metropolitan Area Yanti Budiyantini & Sheilla Alviany The spatiotemporal variable effects of individuals' CO2 emission in Bandung Metropolitan Areas Dimas B.E. Dharmowijoyo & Cynthia D. Maharani Managing the Past into Future: Materiality and Discourse on Cultural LandscapeWijaya Martokusomo Wijaya Martokusumo JIFAM, Vol.3, Issue 2, August 2021 Neighborhood for Adolescent Girls: The Case of Urban Dense Kampong In Yogyakarta City Center Mu’afifah & Setiawan Cengklik Reservoir Tourism Development with approach Eco-Waterfront Auliya Rohmah Ramadhani, Budi Prayitno & Wiwik Setyaningsih Early Chinese Settlements Adaptive Reuse as History and Activity Node at Lasem Living Museum Ardelia J. Cungwin & Widjaja Martokusumo Improvement Strategy for KOTAKU program in Slum Settlements Area in Sidoarjo Ririn Putri Kusuma & Dian Rahmawati Urban Resilience: How to Apply in the Planning and Design Practice? Novi Maulida Ni’mah & Bakti Setiawan